Issues Arising in Psychological Consultations to Help Parents Talk to Minor and Young Adult Children about their Cancer Genetic Test Result: a Guide to Providers. Issue 2 (3rd October 2016) - Patenaude, Andrea Farkas; Schneider, Katherine A.
Abstract: The defining difference between genetic and traditional medicine is that genetic findings have implications not just for the patient, but also for their relatives. Discussion of a test result between parent and child is both a transformative and a translational moment in the life of a family. Parents report wanting help in talking to their children. The challenge for genetic counselors and other providers is to be able to recognize which issues are at the core of parental distress and be able to offer recommendations to empower and support parents. The complexity of potential genetic findings, including variants of uncertain significance (VUS) and incidental findings have vastly increased, requiring considerable explanation and leaving less time for discussion of emotional issues. While the nature of the testing (single gene to multigene panel and genomic testing) is dramatically changing, the nature of parent concerns remains remarkably constant. Families differ in many respects, so no "recipe" suffices to answer parents' questions about how this important task should be approached in each family. Successful consultation to parents requires true counseling, matching parents' fears and questions with information, exploration and advice specific to their concerns, their circumstances and strengths.